2017
DOI: 10.1155/2017/5164594
|View full text |Cite
|
Sign up to set email alerts
|

Nonpenetrating Damage Identification Using Hybrid Lamb Wave Modes from Hilbert-Huang Spectrum in Thin-Walled Structures

Abstract: Lamb waves have shown promising advantages for damage identification in thin-walled structures. Multiple modes of Lamb wave provide diverse sensitivities to different types of damage. To sufficiently utilize damage-related wave features, damage indices were developed by using hybrid Lamb wave modes from Hilbert-Huang spectra. Damage indices were defined as surface integrals of Hilbert-Huang spectra on featured regions determined by time and frequency windowing. The time windowing was performed according to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The results show that the Ort of MCEEMD is better than that of the other two algorithms. [32]. Figure 6 provides the Hilbert-Huang spectrums for three decomposition methods.…”
Section: Analysis Of the Simulation Signal Using Emd Ceemd And Mceemdmentioning
confidence: 99%
“…The results show that the Ort of MCEEMD is better than that of the other two algorithms. [32]. Figure 6 provides the Hilbert-Huang spectrums for three decomposition methods.…”
Section: Analysis Of the Simulation Signal Using Emd Ceemd And Mceemdmentioning
confidence: 99%
“…Authors showed the validity of the approach on a carbon fibre reinforced polymer (CFRP) plate, but it is evident that as the number of sensors used decreases, the level of accuracy decreases. Wang et al [12] in 2017 proposed a method based on the analysis of the difference between a signal in the case of a healthy plate and a damaged one to build damage indices using hybrid Lamb wave modes, with the final purpose of damage localisation. The method is very accurate in localising the damage.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of the Lamb waves usage is small energy losses of the waves during their propagation over long distances. The generation of these waves can be done in either contact [1], [2], [3] or non-contact [4], [5] manner. In turn, the waves detection can also be done in contact [1], [2], [3] or non-contact way [4], [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…The generation of these waves can be done in either contact [1], [2], [3] or non-contact [4], [5] manner. In turn, the waves detection can also be done in contact [1], [2], [3] or non-contact way [4], [6], [7]. Although contact methods are characterized by relatively high amplitudes of the generated signals, they have important drawback, i.e.…”
Section: Introductionmentioning
confidence: 99%